Should We Re-think Regulations and Standards for Lighting at Workplaces? A Practice Review on Existing Lighting Recommendations - Stefani, Oliver; Cajochen, Christian (Frontiers in Psychiatry, 2021)
Nowadays lighting projects often include temporal variations of the light, both spectrally and in terms of intensity to consider non-visual effects of light on people. However, as of today there are no specific regulations. Compliance with common lighting standards often means that only little biological active light reaches the eye. In this practice review we confront existing regulations on visual lighting aspects with new recommendations on non-visual aspects and highlight controversies among them. We conclude with lighting recommendations that address both aspects.